모바일 웹 브라우징 서비스 수용에 관한 연구 - 류성렬(Sung-Yul Ryoo); 김문오(Moon-Oh Kim); 김효진(Hyo-Jin Kim) (한국콘텐츠학회 논문지, 9(2), 2009)
Mobile web browsing services that bring the full PC browsing experience to customer's mobile handset have been emerged. This study is to investigate the intention to use mobile web browsing based on Technology Acceptance Model(TAM) which has been widely used to explain and predict the IT acceptance and incorporated with self-efficacy which was identified as an important determinant of user's new technology adoption in recent literature on technology acceptance. Specifically, from a theoretical perspective, this study not only clarifies mobile self-efficacy, but also develops an instrument to measure the concept of mobile self-efficacy. The results indicate that both computer self-efficacy and mobile self-efficacy directly influence perceived ease of use, and that perceived ease of use enhance perceived usefulness. And the findings indicate that perceived ease of use and usefulness have direct effects on attitude and then it is positively associated with intention to use mobile web browsing. Therefore, the findings imply that mobile self-efficacy can be employed as an important variable in examining user's intention for various mobile services to come in future. 모바일 웹 브라우징 서비스는 컴퓨터 환경에서의 인터넷 경험을 고객의 휴대기기에서 가능하게 해 주는 새로운 서비스이다. 본 연구는 모바일 웹 브라우징 서비스의 사용 의도를 조사하기 위하여 정보기술 수용을 설명하는데 가장 많이 사용되고 있는 기술수용모형(TAM)을 기반으로 하여, 최근 기술수용 문헌에서 중요한 요인으로 인식되고 있는 자기효능감을 컴퓨터 자기효능감과 모바일 자기효능감으로 구분하여 실증 분석을 실시하였다. 특히, 본 연구에서는 기존의 문헌에서 제시되지 않았던 모바일 자기효능감의 개념을 명확히 하고, 이 개념을 측정하기 위한 측정 도구를 개발하였다. 연구 결과는 컴퓨터 자기효능감과 모바일 자기효능감이 사용 용이성에 영향을 미친다는 것을 제시해 주었으며, 기존의 TAM에서 제시한 연구가설이 모두 유의한 것으로 나타났다. 따라서 본 연구에서 제시한 모바일 효능감에 대한 연구 결과는 향후 지속적으로 출현할 다양한 모바일 서비스에 대한 고객의 사용 의도를 분석함에 있어 중요한 변수로서 활용될 수 있을 것이다.